PENGARUH SELF EFFICACY KEWIRAUSAHAAN TERHADAP MOTIVASI WIRAUSAHA PESERTA DIDIK PEMASARAN SMK NEGERI 1 PONTIANAK - Natalia, Anggela; Genjik, Bambang; Syahrudin, Husni (Universitas Tanjungpura, 2023)
The purpose of this study is to find out: 1) How well students perceived entrepreneurial self-efficacy in marketable skill competence of SMK Negeri 1 Pontianak. 2) What is the entrepreneurial motivation of Marketing Competence students at SMK Negeri 1 Pontianak, and 3) To what extent did entrepreneurial self-efficacy influence the entrepreneurial motivation of students participating in the Marketing Specialization Program at SMK Negeri 1 Pontianak. Methods used were quantitative and descriptive methods. A total of 36 populations were randomly sampled. Data analysis used was simple linear regression. The results showed that 1) the students' perceptions of the ability of marketing skills about self-efficacy in entrepreneurship were in the very high category, representing 84.12%; 3) Entrepreneurial self-efficacy perception affects entrepreneurial motivation. The effect of entrepreneurial self-efficacy on students' entrepreneurial motivation in SMK Negeri 1 Pontianak's marketable skill competence was 35.1% from the SPSS 26 calculated results. A significant value was obtained.0.000 0.05, which means that H0 is rejected and Ha is accepted. Therefore, it can be concluded that there is an influence between entrepreneurial self-efficacy and entrepreneurial motivation of students in the market expertise competence of SMK Negeri 1 Pontianak.